2020
DOI: 10.1249/mss.0000000000002344
|View full text |Cite
|
Sign up to set email alerts
|

New Data-based Cutoffs for Maximal Exercise Criteria across the Lifespan

Abstract: Purpose To determine age-dependent cutoff values for secondary exhaustion criteria for a general population free of exercise limiting chronic conditions; to describe the percentage of participants reaching commonly used exhaustion criteria during a cardiopulmonary exercise test (CPET); and to analyze their oxygen uptake at the respective criteria to quantify the impact of a given criterion on the respective oxygen uptake (V˙O2) values. Methods Data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…However, despite the fact that it was surpassed on average at~93% of the bout's ⩒o 2peak , the fact that the criterion value for HR identified 20 of the 23 individuals who did not achieve their ⩒o 2max on RAMP-INC suggests that at least for some individuals, it might have been valid for this purpose. Finally, contrary to our third hypothesis, use of newly-proposed age-dependent values for RER and HR [14] did not improve the ability to identify instances when CWR confirmed that RAMP-INC was characterized by a submaximal ⩒o 2peak . Specifically, use of more stringent RER values yielded the same conclusion (acceptance of ⩒o 2max for 33 of 35 RAMP-INC tests including 23 during which it was confirmed to have not been reached) while use of less stringent HR values resulted in seven additional confirmations of ⩒o 2max on RAMP-INC that included five tests during which the CWR bout refuted that conclusion.…”
Section: Plos Onecontrasting
confidence: 80%
See 3 more Smart Citations
“…However, despite the fact that it was surpassed on average at~93% of the bout's ⩒o 2peak , the fact that the criterion value for HR identified 20 of the 23 individuals who did not achieve their ⩒o 2max on RAMP-INC suggests that at least for some individuals, it might have been valid for this purpose. Finally, contrary to our third hypothesis, use of newly-proposed age-dependent values for RER and HR [14] did not improve the ability to identify instances when CWR confirmed that RAMP-INC was characterized by a submaximal ⩒o 2peak . Specifically, use of more stringent RER values yielded the same conclusion (acceptance of ⩒o 2max for 33 of 35 RAMP-INC tests including 23 during which it was confirmed to have not been reached) while use of less stringent HR values resulted in seven additional confirmations of ⩒o 2max on RAMP-INC that included five tests during which the CWR bout refuted that conclusion.…”
Section: Plos Onecontrasting
confidence: 80%
“…The peak values for each variable were defined as the highest 20-s rolling-average value measured during each test. To evaluate secondary criteria that have traditionally been used for verifying ⩒o 2max during INC, we determined the number of participants who achieved/surpassed an RER of 1.10 and/or a HR of 95% of the age-predicted maximum (220 minus age) on RAMP-INC. To evaluate newly-proposed age-dependent criteria, we determined the number of participants who achieved/surpassed an RER of 1.13, a HR of 96% of the adjusted age-predicted maximum (210 minus age; APMHR 210 ) and/or 93% of the age-predicted maximum based on the formula recommended by Tanaka et al (208 minus 0.7 � age; APMHR 208 ) for aged 20-39 yr or achieved/surpassed an RER of 1.10, a HR of 99% of APMHR 210 and/or 92% of APMHR 208 for aged 40-59 yr [14]. In each case, for these participants, we also determined the ⩒o 2 values that were present at the point at which the RER and HR criterion values were achieved during the test and then expressed them as a percentage of the ⩒o 2peak during RAMP-INC and the higher ⩒o 2peak achieved across both tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Criteria for the attainment ofVO 2max was adjusted for age. However, since not all participants fulfilled to criteria for attainment ofVO 2max, we report this asVO 2peak (Wagner et al, 2020). We reportVO 2peak as the mean of the three highest 10-s values during the test.…”
Section: Discussionmentioning
confidence: 99%